2020
DOI: 10.5194/wes-2020-106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of tilt control for wind-turbine arrays in the atmospheric boundary layer

Abstract: Abstract. Wake redirection is a promising approach designed to mitigate turbine-wake interactions which have a negative impact on the performance and lifetime of wind farms. It has recently been found that substantial power gains can be obtained by tilting the rotors of spanwise-periodic wind-turbine arrays. Rotor tilt is associated to the generation of coherent streamwise vortices which deflect wakes towards the ground and, by exploiting the vertical wind shear, replace them with higher-momentum fluid (high-s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The method suggested to achieve this is individual rotor yaw since it is a well‐established technique; however, the effects of rotor tilt are also of interest 51,52 and could be examined in further works. The effects of pitch and roll in floating turbines may also be applied to the multirotor case, as has been investigated in single rotor wind tunnel studies (for example, 53‐56 ) and numerical studies of Xiao and Yang 57 .…”
Section: Introductionmentioning
confidence: 99%
“…The method suggested to achieve this is individual rotor yaw since it is a well‐established technique; however, the effects of rotor tilt are also of interest 51,52 and could be examined in further works. The effects of pitch and roll in floating turbines may also be applied to the multirotor case, as has been investigated in single rotor wind tunnel studies (for example, 53‐56 ) and numerical studies of Xiao and Yang 57 .…”
Section: Introductionmentioning
confidence: 99%
“…the authors simulated up to three turbines in a column; both studies reported significant power gains at the cluster level, caused by an improved capture downstream that offsets more limited losses upstream. Simulation studies on more complex layouts were conducted by Cossu (2020a) and Cossu (2020b), where the front two rows of turbines in a farm were tilted, obtaining significant power gains at the wind plant level. The author also studied the effect that rotor size, longitudinal spacing between the turbines and thrust setting can have on the plant power output.…”
Section: Introductionmentioning
confidence: 99%
“…To this purpose, CFD simulations of a scaled wind turbine, validated with wind tunnel experiments, are employed. Expanding on previous tilt misalignment studies, which analyzed streamwise spacings of 6-8 rotor diameters (Fleming et al, 2015;Annoni et al, 2017;Cossu, 2020b;Scott et al, 2020), the present work considers distances up to 12 rotor diameters, which is a more realistic spacing for offshore-wind applications. -Make preliminary calculations of the quantity of water ballast that needs to be redistributed for achieving the necessary tilting of the rotor, along with estimating the associated energy expenditure.…”
mentioning
confidence: 99%
“…In the precursor simulation, the ABL is driven by a pressure gradient adjusted to maintain an horizontally-averaged mean of 8m/s from the west at z=100m (a few meters above hub height z h =89m). In the region spanned by the turbines (z <152m) the streamwise mean velocity is well approximated by the logarithmic law and the vertical wind veer is less than 4 o (see Cossu, 2020b, where the same ABL has been already considered).…”
Section: Problem Formulationmentioning
confidence: 99%
“…3b) leading to a stronger downwash which more efficiently exploits the vertical velocity gradient. Smaller values of the optimal tilt angle ϕ would probably be found if C T was held constant instead of β (as in Cossu, 2020b).…”
mentioning
confidence: 99%